2013
DOI: 10.1103/physrevlett.110.117201
|View full text |Cite
|
Sign up to set email alerts
|

Mode- and Size-Dependent Landau-Lifshitz Damping in Magnetic Nanostructures: Evidence for Nonlocal Damping

Abstract: We demonstrate a strong dependence of the effective damping on the nanomagnet size and the particular spin-wave mode that can be explained by the theory of intralayer transverse-spin pumping. The effective Landau-Lifshitz damping is measured optically in individual, isolated nanomagnets as small as 100 nm. The measurements are accomplished by use of a novel heterodyne magneto-optical microwave microscope with unprecedented sensitivity. Experimental data reveal multiple standing spin-wave modes that we identify… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
112
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(120 citation statements)
references
References 34 publications
5
112
3
Order By: Relevance
“…These results can be used to determine the values of saturation magnetization M s ¼ 608 emu cm À 3 , surface magnetic anisotropy K s ¼ 0.237 erg cm À 2 and edge dilution depth D ¼ 10 nm, where D is defined as the distance from the wire edge over which magnetization linearly increases from zero to the full film value 43 . These values of M s , K s and D are consistent with previous studies of thin Py nanomagnets [45][46][47] . Using these values of the nanowire magnetic parameters and assuming translational invariance along the nanowire axis, we perform micromagnetic simulations to find the spectrum of spin wave eigenmodes for magnetic field applied in the sample plane at b ¼ 85°.…”
Section: Resultssupporting
confidence: 92%
“…These results can be used to determine the values of saturation magnetization M s ¼ 608 emu cm À 3 , surface magnetic anisotropy K s ¼ 0.237 erg cm À 2 and edge dilution depth D ¼ 10 nm, where D is defined as the distance from the wire edge over which magnetization linearly increases from zero to the full film value 43 . These values of M s , K s and D are consistent with previous studies of thin Py nanomagnets [45][46][47] . Using these values of the nanowire magnetic parameters and assuming translational invariance along the nanowire axis, we perform micromagnetic simulations to find the spectrum of spin wave eigenmodes for magnetic field applied in the sample plane at b ¼ 85°.…”
Section: Resultssupporting
confidence: 92%
“…In that paper it was found that the S21 value for a stripline loaded by a thin ferromagnetic film scales as exp(Z r /Z 0 ), where Z 0 is the characteristic impedance of the stripline without the sample on its top and Z r is extra impedance inserted by the ferromagnetic resonance in the material. Equation (1) We also add an extra term - (1) S f -to this equation, in order to account for a linear slope seen in S(f) in some traces off-resonance. ( (1) S is also a complex number.)…”
Section: Methodsmentioning
confidence: 99%
“…Equation (1) We also add an extra term - (1) S f -to this equation, in order to account for a linear slope seen in S(f) in some traces off-resonance. ( (1) S is also a complex number.) This formula fits the experimental data very well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimization of MTJ performance for these applications requires quantitative evaluation of the spin torque (ST) vector [12], magnetic damping [13], voltagecontrolled magnetic anisotropy [14][15][16], and the spectrum of magnetic excitations of the MTJ [17,18]. A common techniques for quantitative measurements of these properties is ST ferromagnetic resonance (ST-FMR) [19,20].…”
mentioning
confidence: 99%